Weed control strategies for multiple cropping systems of the humid and subhumid tropics - Akobundu, I.O. (1980)
The bulk of the humid and subhumid tropics of the world lie within 10 north and south of the equator and the greatest land masses of this region are located in South America and Africa. The region consists of those parts of the tropics where precipitation exceeds evapotranspiration in at least seven months of the year, and where total annual rainfall is greater than 1,000 mm (Breitenbach, 1974). The region is characterized by maximum insolation and uniform high temperatures with annual mean averages of between 25 C and 27 C in the lowland areas near the equator. The major soil types in the region are the ultisols, oxisols and alfisols. The ultisols and oxisols are characterized by low base saturation and the alfisols by high base saturation. All these soil groups have low organic matter~ ntent and medium to high acidity (Kellogg and Orvedal, 1969; Donahue~ 1970; Greenland, 1975). These soils are highly weathered and prone to erosion if exposed. Although this region supports luxuriant vegetation, soil fertility is in a delicate balance between rapid plant growth and the breakdown of litter which continues at a high rate throughout the year. Rapid decomposition, however, prevents the accumulation of organic matter in the soil. Thus, any crop production activities that tend to expose the soil for an extended period without adequate soil conservation measures lead to irreversible degradation and yield decline. The climax vegetation is the tropical rain forest, and this merges into savanna with declining rainfall. Some important characteristics of the humid and subhumid tropics are shown in Table 1.